2022
DOI: 10.1037/pag0000667
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity to daily stressors: Does stressor pile-up within a day matter for young-old and very old adults?

Abstract: Over the past decade, many studies have reported individual differences in negative emotional reactions to daily stressful events. However, whether and how individual and age-related differences in emotional reactivity also depend on the temporal characteristics of stressors has received little attention. In this project, we focused on the temporal characteristics of stressor occurrence and examined the pile-up of stressors within a day-referring to multiple stressors encountered within a relatively narrow tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
11
1
1
Order By: Relevance
“…In addition, we were able to contrast these groups which was not done in previous studies (e.g., Wettstein, Wahl, et al, 2021). Previous research with the current sample found no age differences in terms of momentary subjective age variability (Kornadt et al, 2021), and findings in terms of stress reactivity differences between old and very old participants are nuanced (Kunzmann et al, 2022; Schilling et al, 2021). In the current analyses, for those in the very old group, predictive effects of cortisol for momentary subjective age seem to be stronger, even when additionally including comorbidities, which might indicate a stronger linkage between hormonal measures of stress and feeling older for very old participants.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In addition, we were able to contrast these groups which was not done in previous studies (e.g., Wettstein, Wahl, et al, 2021). Previous research with the current sample found no age differences in terms of momentary subjective age variability (Kornadt et al, 2021), and findings in terms of stress reactivity differences between old and very old participants are nuanced (Kunzmann et al, 2022; Schilling et al, 2021). In the current analyses, for those in the very old group, predictive effects of cortisol for momentary subjective age seem to be stronger, even when additionally including comorbidities, which might indicate a stronger linkage between hormonal measures of stress and feeling older for very old participants.…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, the EMIL sample consisted of N = 170 participants ( n = 123 older and n = 47 very old). For further description of the sample and selectivity effects, see Schilling et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…All the young–old and most of the old–old participants were recruited from the ILSE study (see Sattler et al, 2017), with an additional 15 old–old participants recruited from the community via advertisements in local newspapers. As described elsewhere (Schilling et al, 2022), better cognitive test performance at the last wave of ILSE (2014–2017) was the main predictor for taking part in EMIL. The project was approved by the ethics committees of the University of Heidelberg and the German Society for Psychology (Deutsche Gesellschaft für Psychologie [DGPs]) and participants provided written informed consent.…”
Section: Methodssupporting
confidence: 64%
“…The final sample thus consisted of n = 123 young–old participants (66–69 years old, M age = 67.19 years, 47% female) and n = 47 old–old participants (84–90 years old, M age = 86.59 years, 60 % female). For a further description of the sample and selectivity effects, see Schilling et al (2020), details about the study design, procedures, and measures obtained are reported in https://osf.io/nhzpw/?view_only=69f637430e214e168e91f888a8d24dec.…”
Section: Methodsmentioning
confidence: 99%